Standard Operating Procedure (SOP) for hybridization and crossing block management in cassava - Iluebbey, P.; Kulakow, P.; Mbanjo-Edwige, G.; Bakare, D.; Peteti, P.; Toyinbo, S.; Ikpan, S.; Ogungbesan, B.; Mfam, C. (International Institute of Tropical Agriculture, 2024)
Genetic variation is the basis of selection in plant breeding. Hybridization is the process of making controlled crosses between selected genotypes to provide genetic variation for stage 1 of plant breeding. This diversity created in the genetic resources provides an opportunity for plant breeders to develop new and improved cultivars with desirable characteristics.